The impact of online brand community members, brand identification and community identification on participation: The moderating effects of frequency - Ha, Yongsoo (International Journal of Innovative Research and Scientific Studies, 2023)
The effect of online brand communities’ value creation practices on brand identification and community identification was examined using social identity theory as a theoretical background of this study. In examining their relationship, this study defined the practices that relate to the focal brand as both brand use and impression management whereas the practices that relate to the community were defined as both social networking and community engagement. The effects of the two identification constructs (brand and community identification) on participation and their impact on brand awareness were also tested. The effects of frequency as a moderating variable on the relationship between brand identification community identification and participation were also revealed. Structural equations modeling was used to analyze the data collected after an online survey was done. Among the value creation practices, this study revealed that the impression management practice had a significant effect on brand identification and the community engagement practice had a significant effect on community identification. Test results have also shown that community identification has a significant effect on participation. Frequency moderated the relationship between brand identification and participation. In the high frequency group, brand identification had a significant effect on participation whereas in the low frequency group, the effect was not significant.